Perang Armagedon - Lanny Laras (Jurnal Teologi dan Pelayanan Kerusso, 2017)
The Armageddon will be the site of gathering of armies for a battle during end times, variously interpreted as either or symbolic location. The term is also used a generic sense to refer to end of the world scenario. According to the Bible, Jesus will return to earth and defeat the Antichrist, the False prophet and Satan the Devil in the Battle of Armageddon. Then Satan will be put into the “bottomless pit” or abyss for 1,000 years, knows as the Millennium.